1997
DOI: 10.1007/bf02551106
|View full text |Cite
|
Sign up to set email alerts
|

Should we get routine urothelial biopsies in every stone surgery?

Abstract: Physical traumas have been implicated as intrinsic risk factors for the progression of urothelial tumours. In stone disease, histologic changes of the urothelium have a wide spectrum. We want to show the importance of biopsies for identification of these changes. In this study, we investigated the histologic changes of the urothelium in stone patients. There were 16 squamous metaplasia, 14 pyelitis follicularis, 5 pyelitis or ureteritis cystica, 4 polypoid pyelitis or ureteritis, 2 encrusted pyelitis in 43 sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…They proposed that chronic irritation and infection may play a role, because kidney or ureter stones were located on the same side of the body as the tumors in most patients with renal pelvis/ureter cancer evaluated in their study. Ozdamar et al [16] found a high percentage of cell transformation around the stone site when performing endoscopic surgery. Malignant change was also found in their patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They proposed that chronic irritation and infection may play a role, because kidney or ureter stones were located on the same side of the body as the tumors in most patients with renal pelvis/ureter cancer evaluated in their study. Ozdamar et al [16] found a high percentage of cell transformation around the stone site when performing endoscopic surgery. Malignant change was also found in their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant change was also found in their patients. In view of the high risk of renal malignancy in stone patients, Ozdamar et al [16] proposed that biopsy should routinely be performed during stone surgery. Our results show a high percentage of TCC cell type within nonfunctional kidneys caused by stone disease; therefore, we suggest that surgical specimens be taken to pathology for careful evaluation during surgery in order to evaluate whether a more invasive surgery, such as nephroureterectomy, is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Von Brunn's nests with central lumina lined by urothelium or columnar glands are designated ureteropyelitis cystica and ureteropyelitis glandularis, respectively. Such changes are commonly associated with calculi [14]. Simple flat urothelial hyperplasia indicates an increase in the layers of urothelium from the usual three or five to more than seven layers, usually associated with inflammation or neoplasia [11].…”
Section: Discussionmentioning
confidence: 99%
“…All researchers stated that malignant differentiation might be related to long-standing renal stones. It is well known that stone disease causes alterations in the urothelium [14,15] , however it is still a debate to perform routine renal biopsies from the stone-bearing kidneys.…”
Section: Discussionmentioning
confidence: 99%